Estudios de perfiles de profundidad AES y fotoconductividad de películas delgadas de AgInS2 preparadas por co-evaporación (2014)
In this study, thin films of AgInS2 with chalcopyrite-type tetragonal structure were grown by means of a procedure based on the sequential evaporation of metallic precursors in presence of elemental sulfur in a two-stage process. The effect of the growth temperature and the proportion of the evaporated Ag mass in relation to the evaporated In mass (mAg/mIn) on the phase and homogeneity in the chemical composition were researched through X-ray diffraction measurements and Auger electrons spectroscopy. These measurements evidenced that the conditions for preparing thin films containing only the AgInS2 phase, grown with tetragonal chalcopyrite-type structure and good homogeneity of the chemical composition in the entire volume, are a temperature of 500 ºC and a 0.89 mAg/mIn proportion.